Implementasi Peningkatan Kualitas Lingkungan Perusahaan terhadap Kepuasan dan Kinerja Karyawan di PT Madu Baru Yogyakarta - Hilma Harmen; Bintang Emeli Siahaan; Jonathan Delvinosa Gultom; Ketrin Hivisini Simbolon; Marta Marta; Raissa Nazswa Indira; Zizi Zalianty (BADAN PENERBIT STIEPARI PRESS, 2026)
This research aims to analyze the implementation of improving the quality of the work environment on employee satisfaction and performance at PT Madu Baru Yogyakarta. Fluctuations in employee satisfaction and performnce influenced by less-than-optimal working conditions, such as noise, waste odors, uneven room temperature, and untidy workspace arrangement. The research method used is qualitative with a literature study approach thru the analysis of various relevant journals and books. The research results indicate that the work environment, both physical (lighting, cleanliness, air circulation, safety) and non-physical (interpersonal relationships and communication), positively influences increased employee satisfaction. This satisfaction serves as an important factor driving motivation, loyalty, and improved performance. Therefore, improving the quality of the work environment needs to be done thru strategic steps, such as spatial layout improvements, temperature and noise control, increased cleanliness, and building open communication and creating harmonious working relationships among employees. These efforts are expected to create a comfortable and productive work environment, thus supporting employee satisfaction while also sustainably strengthening company performance.